2023
DOI: 10.1080/22423982.2023.2213909
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with healthcare avoidance during the COVID-19 pandemic among the Sámi in Sweden: the SámiHET study

Abstract: The aim of this population-based cross-sectional study was to assess the prevalence of healthcare avoidance during the COVID-19 pandemic and its associated factors among the Sámi population in Sweden. Data from the “Sámi Health on Equal Terms” (SámiHET) survey conducted in 2021 were used. Overall, 3,658 individuals constituted the analytical sample. Analysis was framed using the social determinants of health framework. The association between healthcare avoidance and several sociodemographic, material, and cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Also, health care avoidance did not differ between Sámi and non-Sámi in Sweden during the first year of the pandemic. However, risk groups for such avoidance among the Sámi included Sámi women, young Sámi (18–29 years of age), Sámi living outside Sápmi, Sámi with low income and Sámi experiencing economic stress [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, health care avoidance did not differ between Sámi and non-Sámi in Sweden during the first year of the pandemic. However, risk groups for such avoidance among the Sámi included Sámi women, young Sámi (18–29 years of age), Sámi living outside Sápmi, Sámi with low income and Sámi experiencing economic stress [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has investigated how the COVID-19 pandemic has affected the Arctic populations beyond a strictly medical perspective, for example examining impacts on mental health and well-being, regional economies, social and cultural environments, knowledge production, mobility, impacts on food security and other social issues [ 19 ]. However, Spence & Krishnan [ 19 ] found that articles investigating the pandemic-related social dynamics in Indigenous Arctic populations mostly concern the Canadian northern context, and we are unaware of English language articles elucidating how the pandemic affected the Sámi in Sweden, aside from two studies using the SámiHET public health questionnaire data [ 17 , 18 ]. Therefore, in order to understand and learn from how the Sámi in Sweden experienced the pandemic, empirical evidence is needed.…”
Section: Introductionmentioning
confidence: 99%